2019
DOI: 10.1177/0047287519874126
|View full text |Cite
|
Sign up to set email alerts
|

Risk Types and Coping Mechanisms for Ethical Tourism Entrepreneurs: A New Conceptual Framework

Abstract: Risk is a widely accepted entrepreneurial construct and entrepreneurship is a key feature of the tourism industry. Yet, investigating types of risks and calls for research on ethical entrepreneurship in tourism have largely been neglected. This research provides an original contribution to academia about risk-types and subsequent coping mechanisms as faced by ethical tourism entrepreneurs. Using methods from Personal Construct Theory, 15 in-depth interviews with self-defined ethical tourism entrepreneurs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 76 publications
0
11
0
1
Order By: Relevance
“…Two dominant traits are the reliance on local resources available for free or little cost and the tendency of activity providers to be proactive and seek actionable opportunities in their environment. Thus, spatial bricolage could help to mitigate the functional and monetary risks tourism entrepreneurs face (Power et al, 2019). Moreover, we found that personal contacts with locally embedded actors and pubic bodies facilitate resource mobilisation.…”
Section: Resource Transfermentioning
confidence: 74%
See 1 more Smart Citation
“…Two dominant traits are the reliance on local resources available for free or little cost and the tendency of activity providers to be proactive and seek actionable opportunities in their environment. Thus, spatial bricolage could help to mitigate the functional and monetary risks tourism entrepreneurs face (Power et al, 2019). Moreover, we found that personal contacts with locally embedded actors and pubic bodies facilitate resource mobilisation.…”
Section: Resource Transfermentioning
confidence: 74%
“…Informal understandings enable access to resources, but the owner-managers of the studied tourism micro-firms appreciate the legitimacy coming from formal agreements. Validation of their activity, the sense that it is alright to use local resources the way they do, reduces uncertainty and the functional risk associated with lack of control over resources (Power et al, 2019). Resource transfer might require the involvement of a mediating actor to bridge over possible power imbalances between the entrepreneur and other stakeholders.…”
Section: Resource Transfermentioning
confidence: 99%
“…Upon reviewing mechanism-related studies (e.g. Power, Di Domenico, & Miller, 2019 ; Ruan, Li, Zhang, & Liu, 2019 ; Tsai & Chen, 2010 ), it was concluded that a ‘mechanism’ is a method or a system of organizing different variables to clarify the relationships among them and solve certain problems or achieve a goal. In the current study, ‘mechanism’ refers to the connecting logic between psychological distance and perceived risk.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is also a significant body of research on generic tourism entrepreneurship (Fu, Okumus, Wu and Köseoglu 2019;Thomas et al 2011), yet with virtually no significant engagement with innovation, risk and uncertainty. For tourism entrepreneurs, these issues are of crucial importance and require further examination as: 1) small firms dominate the tourism industry, which are on the one hand a hotbed of innovative practices and on the other hand have limited resources and therefore are especially vulnerable to uncertainty and risk (Verreynne et al 2019;Power, Di Domenico and Miller, 2019); 2) there is evidence that industrial dynamics and industry effects can significantly influence the level of risk and uncertainty and entrepreneurial behavior (Shepherd 2015), but research on tourism innovation is still relatively thin; 3) tourism entrepreneurs operate in highly contested markets which increase uncertainties (Verreynne et al 2019) and they are vulnerable to external shocks in major markets or the supply chain (Ritchie 2004); 4) the temporality of demand is an important determinant of firm performance (Park, et al 2016) and therefore likely to be a focus of innovation among tourism firms; 5) a significant number of tourism entrepreneurs, often described as "lifestyle entrepreneurs", create innovative products and serve niche markets (Ateljevic and Doorne 2000), which together with the strong intertwining of market uncertainty and firm-specific uncertainty (Aarstad, Ness, and Haughland 2015), has significant influence on the risk and uncertainty they face. The roles of risk and uncertainty in tourism entrepreneurship and innovation have been recognised at the conceptual level (Hall and Williams 2008;Williams and Baláž 2014).…”
Section: Introductionmentioning
confidence: 99%
“…There is also a significant body of research on generic tourism entrepreneurship (Fu et al 2019; Thomas, Shaw, and Page 2011), yet with virtually no significant engagement with innovation, risk, and uncertainty. For tourism entrepreneurs, these issues are of crucial importance and require further examination as (1) small firms dominate the tourism industry, which are on the one hand a hotbed of innovative practices and on the other hand have limited resources and therefore are especially vulnerable to uncertainty and risk (Verreynne et al 2019; Power, Di Domenico and Miller 2019); (2) there is evidence that industrial dynamics and industry effects can significantly influence the level of risk and uncertainty and entrepreneurial behavior (Shepherd 2015), but research on tourism innovation is still relatively thin; (3) tourism entrepreneurs operate in highly contested markets that increase uncertainties (Verreynne et al 2019) and they are vulnerable to external shocks in major markets or the supply chain (B. W. Ritchie 2004); (4) the temporality of demand is an important determinant of firm performance (S.…”
Section: Introductionmentioning
confidence: 99%